Identifying The Model of Commitment of Pesantren Teachers in Strengthening the Pesantren Curriculum - Rasyidin, Rasyidin; Prasteyo, Muhammad Anggung Manumanoso; Ritonga, Abdullah Sani; Naeem, Ayesha Fakhar (Eduprof : Islamic Education Journal, 2025)
Teachers ' commitment is the main driving force behind establishing pesantren education services. This research aims to identify a model of teacher commitment to curriculum enhancement. The study is qualitative, utilizing descriptive survey methodologies. According to the study's findings, data was collected through interviews with five informants, including Leaders, Coordinators, and various senior instructors. Pesantren's curriculum is structured around five orientations: holistic, skill development, based on local wisdom, character-oriented, and field-project-based. This perspective appears in the official and hidden curricula and is implemented through direct learning methods. Teachers' commitment to this pesantren is divided into three categories: affective commitment, which has an emotional influence; normative commitment, which demonstrates pedagogical characteristics; and continuous commitment, which prioritizes the pesantren's interests. Combining all of these factors leads to the efficacy of the educational program. The close bond among instructors at the Ar Raudlatul Hasanah and Darul Arafah Islamic Boarding School in Medan increases their dedication to the organization and improves the quality of education delivered to pupils. According to research conducted on these pesantren, social support, a sense of belonging, participation in professional growth, and a mentorship system all play a vital role in building a happy and effective educational environment. The study has implications for developing group activities that create friendship among teachers to foster commitment and the spirit of togetherness.